New Method for Calculating the Settlement of Single Pile and Pile Group in Soft Soil Area - Jingjing Xu; Xu Xu; Wenjuan Yao (Advances in Civil Engineering)
This paper fits the τ-z curve of a single pile by mathematical methods. Based on the one-dimensional similarity of the τ-z curves, the τ-z curves of single pile under different loads are derived. It studies the distribution of the axial force of a single pile by taking the self-weight of the pile and the pile-end resistance ratio into account and establishes the calculated equation of settlement for single pile. The mutual reinforcing effect between the piles is fully considered, and the settlement of each foundation pile in the pile group is deduced in use of shear displacement method. The example analysis shows that the axial force distribution of single pile considering the self-weight and the pile-end resistance ratio is in good agreement with the experimental data. The settlement error of a single pile calculated by the traditional method is 18.52% compared with measured value. When the self-weight and end resistance ratio are not considered, the error reaches 2.26%. However, the error could reduce to 1.64% when they are taken into consideration. It has a good applicability to calculate the settlement of pile group through the τ-z curves of single pile. Also, it can better forecast the settlement behavior of the pile group under similar conditions.